2019
DOI: 10.1002/1873-3468.13686
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of CD133 inhibits GLUT1‐mediated glucose transport through downregulation of the HER3/Akt/mTOR pathway in colon cancer

Abstract: Cluster of differentiation 133 (CD133) is a transmembrane glycoprotein that has been reported as a marker of cancer stem cells or cancer‐initiating cells in various cancers. However, its contribution to tumorigenesis and differentiation remains to be elucidated. To determine the role of CD133 in colon cancer, we silenced CD133 in human colon cancer cells. Silencing of CD133 results in decreased cell proliferation, survival, migration, invasion, and glucose transport. These effects are mediated by downregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…CD133 avoids EGFR endocytosis and sustains EGFR-mediated Akt activation [ 68 , 69 ]. CD133 silencing decreases HER3 levels and suppresses EGFR and HER2 activation without disturbing their gene transcription in CRC cell lines [ 70 ]. CD133 silencing reduces proliferation, clonogenic capacity, migration, cell invasion, and resistance in CRC in part through decreasing glucose uptake as a result of the low GLUT1 expression because of impaired HER3/Akt pathway involved in protein synthesis via mTOR and mRNA stability, probably through the regulation of RNA-binding proteins [ 70 , 71 ].…”
Section: Cd133 Biological Function (Signaling Pathways)mentioning
confidence: 99%
See 1 more Smart Citation
“…CD133 avoids EGFR endocytosis and sustains EGFR-mediated Akt activation [ 68 , 69 ]. CD133 silencing decreases HER3 levels and suppresses EGFR and HER2 activation without disturbing their gene transcription in CRC cell lines [ 70 ]. CD133 silencing reduces proliferation, clonogenic capacity, migration, cell invasion, and resistance in CRC in part through decreasing glucose uptake as a result of the low GLUT1 expression because of impaired HER3/Akt pathway involved in protein synthesis via mTOR and mRNA stability, probably through the regulation of RNA-binding proteins [ 70 , 71 ].…”
Section: Cd133 Biological Function (Signaling Pathways)mentioning
confidence: 99%
“…CD133 silencing decreases HER3 levels and suppresses EGFR and HER2 activation without disturbing their gene transcription in CRC cell lines [ 70 ]. CD133 silencing reduces proliferation, clonogenic capacity, migration, cell invasion, and resistance in CRC in part through decreasing glucose uptake as a result of the low GLUT1 expression because of impaired HER3/Akt pathway involved in protein synthesis via mTOR and mRNA stability, probably through the regulation of RNA-binding proteins [ 70 , 71 ]. Enrichment RNA analysis showed that CD133 + cells in gastric cancer have high expression of RNA-modifying enzymes that modulate RNA decay, mRNA translation, pre-mRNA processing, and RNA export compared to CD133-negative cells [ 72 ]; however, the precise role of CD133 in mRNA processing is unclear.…”
Section: Cd133 Biological Function (Signaling Pathways)mentioning
confidence: 99%
“…45 S6K1 acts as the core effector protein downstream of AKT, mediating protein transcription and positively correlates with the activity of AKT signaling. 46,47 However, whether activation of AKT signaling results in aberrant GLUT1 expression in GC still needs to be elucidated.…”
Section: Dovepressmentioning
confidence: 99%
“…26 Furthermore, an apparent positive association between GLUT1 and p-S6K1 indicated that the AKT-S6K1 axis plays a role in the effect of GLUT1 on GC. 46,[49][50][51] Subgroup survival analysis of GC patients based on p-S6K1 and GLUT1 expression showed that GLUT1 overexpression could be the governing factor upstream of AKT-S6K1. Because GC patients with p-S6K1(+) had worse prognosis than those with p-S6K1(-), GLUT1(+)/p-S6K1(+) also showed a lower survival probability to patients who showed a low negative expression of GLUT1 or p-S6K1.…”
Section: Dovepressmentioning
confidence: 99%
“…AKT/mTOR signaling pathway suffers the most mutations in cancer, being a link between obesity and cancer (especially breast and colon) (26)(27)(28)(29). Steroid hormones, namely estrogens, progesterone, androgens and adrenal steroids are associated with obesity and the development of certain types of neoplasms in women (30).…”
Section: Obesity and Cancermentioning
confidence: 99%